2013
DOI: 10.1134/s0021364012230063
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear BFKL dynamics: Color screening vs. gluon fusion

Abstract: A feasible mechanism of unitarization of amplitudes of deep inelastic scattering at small values of Bjorken x is the gluon fusion. However, its efficiency depends crucially on the vacuum color screening effect which accompanies the multiplication and the diffusion of BFKL gluons from small to large distances. From the fits to lattice data on field strength correlators the propagation length of perturbative gluons is R c ≃ 0.2 − 0.3 fermi. The probability to find a perturbative gluon with short propagation leng… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 35 publications
(57 reference statements)
0
18
0
Order By: Relevance
“…In [9] we found that the choice R c = 0.26 fm leads to a very good description of the DIS data on the proton structure function F 2 (x, Q 2 ) at small x. Applying the color dipole factorization to σ pp tot we observe (see Fig.…”
Section: Vacuum Color Screening and CD Bfklmentioning
confidence: 81%
See 3 more Smart Citations
“…In [9] we found that the choice R c = 0.26 fm leads to a very good description of the DIS data on the proton structure function F 2 (x, Q 2 ) at small x. Applying the color dipole factorization to σ pp tot we observe (see Fig.…”
Section: Vacuum Color Screening and CD Bfklmentioning
confidence: 81%
“…At superhigh energies, E Lab > 10 4 − 10 5 GeV, the perturbative component starts taking over and its unitarization becomes a central issue. In [8,9,10] it was demonstrated that the non-linear, i.e., unitarity effects are very sensitive to the IR regularization which defines a transition between the nonperturbative and perturbative domains. Empirically, the bulk of the total cross section at E Lab ∼ 10 4 −10 5 GeV comes from the nonperturbative domain and our analysis suggests rather small, infrared cutoff for the perturbative contribution, R c = 0.26 fm.…”
Section: Vacuum Color Screening and CD Bfklmentioning
confidence: 99%
See 2 more Smart Citations
“…The perturbative gluons with short propagation length do not walk to large distances, where they supposedly fuse together [6]. The fusion probability appears to be controlled by the dimensionless parameter R 2 c /8B, where B stands for the diffraction cone slope [7,8]. In this communication we discuss the BFKL [2], BK [6] phenomenology of DIS in presence of finite correlation length R c with particular emphasis on a sharpened sensitivity of the non-linear effects to the infrared.…”
Section: Introductionmentioning
confidence: 99%